2020
DOI: 10.3389/fgene.2020.00319
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Ribosomal DNA Promoter Methylation Levels Are Correlated With Paternal Aging and May Relate With in vitro Fertilization Outcomes

Abstract: The impact of aging on reproductive outcomes has received considerable critical attention; however, there is much less information available on the effects of paternal age compared to the effects of maternal age. In this study, methylation levels of sperm rDNA promoter regions and Long Interspersed Nucleotide Element 1 (LINE-1) were measured using pyrosequencing and fertilization, day 3 good-quality embryo, pregnancies, and implantation results were assessed. We observed significantly increasing levels of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The father’s advanced age also correlates with abnormal sperm DNA methylation that is not only confined to differentially methylated regions, but widespread in the genome, especially at the level of regions associated with the control of schizophrenia and/or bipolar disorders [ 166 ]. Interestingly, the methylation of ribosomal DNA increases with age in both somatic and sperm cells, thus influencing nucleolar formation and embryo development [ 167 ].…”
Section: Diet Aging and Environmental Pollution Damage Sperm Qualmentioning
confidence: 99%
“…The father’s advanced age also correlates with abnormal sperm DNA methylation that is not only confined to differentially methylated regions, but widespread in the genome, especially at the level of regions associated with the control of schizophrenia and/or bipolar disorders [ 166 ]. Interestingly, the methylation of ribosomal DNA increases with age in both somatic and sperm cells, thus influencing nucleolar formation and embryo development [ 167 ].…”
Section: Diet Aging and Environmental Pollution Damage Sperm Qualmentioning
confidence: 99%
“…A model involving 15 of the most robust CpGs showed a correlation between the predicted epigenetic age and chronological age ( r = 0.67, median absolute difference between predicted and chronological age 2.91). In a similar study using 60 couples who underwent IVF, a positive correlation was found between the methylation of 21 CpG sites in sperm rDNA promoter and donor age, but no statistically significant correlation was observed between rDNA methylation and IVF outcomes (successful fertilization, Day 3 good-quality embryos, clinical pregnancies) ( Li et al , 2020 ). It should be noted that the rDNA methylation clock gives a lower correlation compared with the epigenetic clock of Jenkins et al described above ( Jenkins et al , 2018 ).…”
Section: Age-associated Epigenetic Changes and Epigenetic Clocks In H...mentioning
confidence: 93%
“…Moreover, evidence showed that sperm from older men had more hypermethylated than hypomethylated CpG sites [50]. Additionally, the level of DNA hypermethylation in the rDNA promoter region of sperm increased significantly with age [51].…”
Section: Dna Methylation and Senescent Spermatozoamentioning
confidence: 99%